2007
DOI: 10.1111/j.1540-8167.2007.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Statins and Renin‐Angiotensin System Blockers on Atrial Fibrillation Recurrence Following Antral Pulmonary Vein Isolation

Abstract: Even though statins and RAS blockers possess anti-inflammatory properties, they did not decrease the recurrence of AF following ablation. However, the subset of patients taking ARB exhibited a trend towards lower AF recurrence. Larger, randomized studies are needed to address this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 41 publications
1
70
0
Order By: Relevance
“…In particular, isolation of the pulmonary veins was the end point for a minority (35%) of the patients. A similar study by Al Chekakie et al [24] demonstrated a favorable outcome with ARBs, though it was not statistically significant due to a limited number of patients. As in the Richter et al [23] study no effect could be attributed to the intake of statins.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, isolation of the pulmonary veins was the end point for a minority (35%) of the patients. A similar study by Al Chekakie et al [24] demonstrated a favorable outcome with ARBs, though it was not statistically significant due to a limited number of patients. As in the Richter et al [23] study no effect could be attributed to the intake of statins.…”
Section: Discussionmentioning
confidence: 91%
“…Al Chekakie et al retrospectively evaluated the recurrence rate of AF in 177 (mean age 56 ± 11 years) consecutive patients who underwent catheter ablation for paroxysmal (132 patients) or persistent (45 patients) AF [68]. Recurrence of AF was defined as an electrocardiographically documented episode lasting at least 30 s, irrespective of symptoms.…”
Section: In Patients Treated With Catheter Ablationmentioning
confidence: 99%
“…6,8,[16][17][18][19] On the other hand, a suppressive effect of RASIs on AF recurrences after PVI was demonstrated in patients with a relatively small LA. 15,20 The present study showed that the use of RASIs was closely associated with the AF recurrence-free rates in the patients with a non-dilated LA, but not at all in the patients with a dilated LA.…”
Section: La Size and Fibrosismentioning
confidence: 99%
“…[16][17][18][19][20][21] A few retrospective trials have demonstrated that the routine use of statins, ACEIs or ARBs did not improve the outcome of AF ablation among patients with drug-resistant paroxysmal or persistent. 16,17 Tayebjee et al also recently identified that RASIs had no beneficial effect on the long-term sinus maintenance after catheter ablation of PAF and PerAF. 18 Zheng et al showed that RASIs could not prevent AF recurrences in patients with chronic AF.…”
Section: Effect Of Rasis On Af Recurrences As Compared With Previous mentioning
confidence: 99%